Hubungan Dukungan Keluarga dengan Motivasi Kontrol Rutin pada Pasien Hipertensi di Wilayah Kerja Puskesmas Samuda - Fitriyati Ulfah; Dwi Agustian Faruk Ibrahim; Ayu Puspita (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Family support is a way to provide assistance to other family members, either morally or materially. Motivation is the feeling or thought that drives someone to behave or engage in activities to achieve goals. Hypertensive patients often neglect regular follow-up visits because they feel fine and have no complaints. This study aims to determine the relationship between Family Support and Motivation for Regular Check-Ups in Hypertensive Patients in the Working Area of Samuda Health Center. Methods: This research used a quantitative method with a descriptive correlational approach. The correlation design utilized a cross-sectional method to determine the correlational relationship between two variables, emphasizing the measurement of both independent and dependent variables at one point in time. The instruments were questionnaires, and the statistical test used was Spearman Rank, which involved 53 hypertensive patients in the Working Area of Samuda Health Center as respondents. Results: The study on Family Support revealed that the highest Crosstabulation result was found in respondents with moderate motivation for regular check-ups, with 21 respondents (75.0%), followed by good motivation with 13 respondents (68.4%), and low motivation with 6 respondents (21.4%). The Spearman Rank statistical test yielded a p-value ≤ 0.000, meaning the p-value was less than 0.05. Thus, H0 was rejected, and Ha was accepted, indicating a significant relationship between Family Support and Motivation for Regular Check-Ups in Hypertensive Patients. Conclusion: There is a significant relationship between Family Support and Motivation for Regular Check-Ups in Hypertensive Patients. It is suggested that healthcare workers enhance family support to improve the motivation for regular check-ups among hypertensive patients in the Working Area of Samuda Health Center through health promotion initiatives.